THEORETICAL ASPECTS REGARDING PUBLIC EXPENDITURES - ANA-PETRINA PĂUN; PETRE BREZEANU (Annals of the University of Petrosani: Economics)
The first part of this work will treat the theoretical aspects of public expenditures. Taking the state as primary supplier of public goods, we have presented the concepts revolving around public and private goods, the theory of pure public goods, the four categories of goods and services, ”club theory”etc. In the second part we analyse different concepts regarding public expenditures from an economic point of view, the subsystems of public expenditures, public versus budgetary expenditures, respectively public versus private expenditures.